Selective modulation through the glucocorticoid receptor ameliorates muscle pathology in mdx mice. Issue 2 (10th September 2013) - Huynh, Tony; Uaesoontrachoon, Kitipong; Quinn, James L; Tatem, Kathleen S; Heier, Christopher R; Van Der Meulen, Jack H; Yu, Qing; Harris, Mark; Nolan, Christopher J; Haegeman, Guy; Grounds, Miranda D; Nagaraju, Kanneboyina
Abstract: The over‐expression of NF‐ κ B signalling in both muscle and immune cells contribute to the pathology in dystrophic muscle. The anti‐inflammatory properties of glucocorticoids, mediated predominantly through monomeric glucocorticoid receptor inhibition of transcription factors such as NF‐ κ B (transrepression), are postulated to be an important mechanism for their beneficial effects in Duchenne muscular dystrophy. Chronic glucocorticoid therapy is associated with adverse effects on metabolism, growth, bone mineral density and the maintenance of muscle mass. These detrimental effects result from direct glucocorticoid receptor homodimer interactions with glucocorticoid response elements of the relevant genes. Compound A, a non‐steroidal selective glucocorticoid receptor modulator, is capable of transrepression without transactivation. We confirm the in vitro NF‐ κ B inhibitory activity of compound A in H‐2K b ‐tsA58 mdx myoblasts and myotubes, and demonstrate improvements in disease phenotype of dystrophin deficient mdx mice. Compound A treatment in mdx mice from 18 days of post‐natal age to 8 weeks of age increased the absolute and normalized forelimb and hindlimb grip strength, attenuated cathepsin‐B enzyme activity (a surrogate marker for inflammation) in forelimb and hindlimb muscles, decreased serum creatine kinase levels and reduced IL‐6, CCL2, IFN γ, TNF and IL‐12p70 cytokine levels in gastrocnemius (GA) muscles. Compared with compound A, treatment with prednisolone, a classical glucocorticoid, in both wild‐type and mdx mice was associated with reduced body weight, reduced GA, tibialis anterior and extensor digitorum longus muscle mass and shorter tibial lengths. Prednisolone increased osteopontin (S pp1 ) gene expression and osteopontin protein levels in the GA muscles of mdx mice and had less favourable effects on the expression of Foxo1, Foxo3, Fbxo32, Trim63, Mstn and Igf1 in GA muscles, as well as hepatic Igf1 in wild‐type mice. In conclusion, selective glucocorticoid receptor modulation by compound A represents a potential therapeutic strategy to improve dystrophic pathology. Copyright © 2013 Pathological Society of Great Britain and Ireland. Published by John Wiley & Sons, Ltd.